1978
DOI: 10.1038/274756a0
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological evidence for causal relationship between Epstein-Barr virus and Burkitt's lymphoma from Ugandan prospective study

Abstract: Results from a prospective sero-epidemiological study initiated in Uganda in 1971 indicate that children with high antibody titres to Epstein-Barr virus structural antigens are at high risk of developing Burkitt's lymphoma. These findings strongly support a causal relationship between the Epstein-Barr virus and Burkitt's lymphoma but suggest that the oncogenic potential of the virus is realised only in exceptional circumstances.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
195
1
4

Year Published

1995
1995
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 540 publications
(218 citation statements)
references
References 33 publications
18
195
1
4
Order By: Relevance
“…Because 98% of the high endemic BLs are EBV positive, the probability that a B cell turns into a BL cell is higher if it carries the virus. Prospective epidemiological studies are also consistent with a contribution of a heavy EBV load to the genesis of the lymphoma (3). BLs usually carry multiple viral episomes.…”
supporting
confidence: 52%
“…Because 98% of the high endemic BLs are EBV positive, the probability that a B cell turns into a BL cell is higher if it carries the virus. Prospective epidemiological studies are also consistent with a contribution of a heavy EBV load to the genesis of the lymphoma (3). BLs usually carry multiple viral episomes.…”
supporting
confidence: 52%
“…[29][30][31] Although no major loci were significantly associated with any of these pathogen burden measures, there was suggestive evidence for association and/or linkage on chromosomes 8 and 11, including a genetic variant in the oncogene MYEOV for all herpes viruses (various herpes viruses are shown to contribute to the development of cancers, eg, EBV to Burkitt's lymphoma and Hodgkin's lymphoma). 32,33 In summary, this study identified a variant on chromosome 20 that is significantly associated with anti-C. pneumoniae IgG. However, no other antibody level traits obtained genome-wide significance levels of association.…”
Section: Discussionmentioning
confidence: 81%
“…Living in regions of malaria endemicity was a predictor of this early age of primary infection. This aberrant primary EBV infection may set the stage for lymphoma development, as previously hypothesized (4)(5)(6).…”
mentioning
confidence: 68%